On Principles In Sadi Carnot’s Thermodynamics (1824). Epistemological Reflections - Pisano, Raffaele (Almagest, 2010)
Abstract In 1824 Sadi Carnot published Réflexions sur la Puissance Motrice du Feu in which he founded almost the entire thermodynamics theory. Two years after his death, his friend Clapeyron introduced the famous diagram PV for analytically representing the famous Carnot’s cycle: one of the main and crucial ideas presented by Carnot in his booklet. Twenty-five years later, in order to achieve the modern version of the theory, Kelvin and Clausius had to reject the caloric hypothesis, which had influenced a few of Carnot’s arguments. Relying on the possibility of studying the history of science by means of logical investigation, in this paper I shall propose an historical/epistemological research on Sadi Carnot’s original thermodynamics theory in which the French scientist presents more than two principles, all of which are expressed by double negated sentences (generally speaking) within non-classical logic.